2022
DOI: 10.22581/muet1982.2204.12
|View full text |Cite
|
Sign up to set email alerts
|

Adapted flower pollination algorithm for a standalone solar photovoltaic system

Abstract: This Extraction of the maximum electrical power from a solar photovoltaic (PV) system under numerous weather conditions is required to reduce its payback time period, per unit energy price, and to compensate for the high initial price of the solar PV system. This could only be achieved by continuously operating the solar PV system at its maximum power point (MPP) under several weather conditions. Unlike under uniform weather conditions (UWC), identification of the real MPP (Global MPP) under partial shading co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In [25], the author suggested an additional filtration and distribution procedure called Random walk in addition to the ordering of solutions to develop a new algorithm called Ordered Flower Pollination Algorithm. The proposed algorithm (Ordered FPA) has outperformed the well-known FPA algorithm [26] under different weather circumstances. Ref.…”
Section: Introductionmentioning
confidence: 96%
“…In [25], the author suggested an additional filtration and distribution procedure called Random walk in addition to the ordering of solutions to develop a new algorithm called Ordered Flower Pollination Algorithm. The proposed algorithm (Ordered FPA) has outperformed the well-known FPA algorithm [26] under different weather circumstances. Ref.…”
Section: Introductionmentioning
confidence: 96%
“…It supplies electricity to consumers throughout the day and uses a grid-tie mechanism to export excess energy to the grid [9,10]. Solar cell power generation is direct dependent on the sun irradiance on collector plane and inverse in relation with the temperature, high temperature decreases the efficiency of solar cell [11,12]. As a result, distributed power generation through solar or wind reduces line losses and the energy issue in remote parts of SAARC countries [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Metaheuristic algorithms, which are inspired by nature and human intelligence, offer great advantages in dealing with problems such as nonlinear optimization problems and thus have gradually become a hot research topic for researchers. Reference 29 31 proposed three improved flower pollination algorithms and conducted performance tests under changing weather conditions, which showed that the improved algorithms substantially improved the tracking speed and tracking efficiency. Reference 32 proposed a grid-connected PV MPPT technique using an arithmetic optimization algorithm to optimize the parameters of the proportional-integral (PI) controller, but the introduction of the PI controller increased the complexity of the system.…”
Section: Introductionmentioning
confidence: 99%